How can Generative Artificial Intelligence (AI) be Effectively Incorporated into Middle School Art Students to Develop Creative Thinking and Enhance A Sense of Community? - Jakobsen, Joyce (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2025)
As a middle school educator, I enhance student creativity through visual expression, weaving ideas into education’s cultural tapestry using emerging technologies like generative AI. Post-pandemic research highlights a need for connection and belonging. Writing and art foster this connection, building creative confidence and self-efficacy. This qualitative analysis explores how generative AI can revitalize instruction by supporting creative learning, particularly for art and language educators. Grounded in Vygotsky’s Zone of Proximal Development, the study focuses on three key challenges: (1) Students often hesitate to begin due to perceived limitations—AI tools can help them visualize ideas and start creating. (2) Learning may feel intimidating—AI can introduce novelty and collaborative projects to boost engagement. (3) Diverse student needs—AI can personalize learning, supporting ESL students by scaffolding understanding, enhancing critical thinking, and adapting to learning pace. This research aims to guide educators and developers in designing tools that empower student voice, creativity, and expression.